Numerical Modelling of Social Media Addiction Cases Using 15th Order Runge-Kutta - Fatahillah, Arif; Prihandini, Rafiantika Megahnia; Hidayatullah, Arfan; Setiawani, Susi; Adawiyah, Robiatul (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2025)
The advancement of information technology has led to more and more people, especially teenagers, becoming addicted to using various social platforms. Despite being a very useful application for social interaction, the habit of spending excessive time on social media is prone to addiction so that teenagers can experience anxiety disorders, depression, health problems, and more. The purpose of this study is to determine the effectiveness of the 15th-order Runge-Kutta method in solving mathematical models in the case of social media addiction. The method used in this research uses experimental research and data collection is done by systematically observing and recording the research indicators. The research was conducted by observing the error, number of iterations, running time, and graphs. In this study, adolescents aged 15-18 years were divided into three compartment states which were modeled into mathematical equations. The results of this study indicate that the 15th order Runge-Kutta method is more effective for solving mathematical models on social media addiction compared to Ordinary Differential Equation (ODE).